Európai kihívások - regionális válaszok: a hagyományok és az innováció sajátosságai a humánerő regionális önszerveződésében - Láczay, Magdolna (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Statistical data in the Region of the Northern Great Plains shows high number of disad-vantaged people, unemployment and ethnic diversity for decades. On the other hand entre-preneurial approach, willingnes for self education and self employment are important char-acteristics of the region. As borderland of the European Union the region is prone to a number of economical, social and development related conflicts. These problems are to be solved locally. Research in this most disadvantaged Eastern region of the country show high numbers of self employed people. Among this group family traditions, higher educa-tion, and willingness to follow the development of their profession made it an elite-like group. This local elite has all the assets elite groups usually have and they put these assets in action. The two leading assets are knowledge and taking the lead in the local society.